Amundsen and the crew of the "Norge," June 27, 1926 - Webster & Stevens
In June 1926, sixteen men crossed the North Pole from Norway to Alaska in the airship "Norge". The group was headed by polar explorers Roald Amundsen and Lincoln Ellsworth, and the dirigible was designed and piloted by Umberto Nobile. On their way back to Europe, the men stopped in Seattle, where they were greeted by over 5,000 cheering people. In this photo, the polar explorers Roald Amundsen (left), Lincoln Ellsworth (middle), and Umberto Nobile (right) sit in deck chairs in front of the crew of the airship "Norge". They are gathered on the deck of the steamship "Victoria" which brought them from Nome to Seattle after their transpolar trip. Nobile holds his dog Titina. 1 negative: glass, b&w; 5 x 7 in.